DGI-032 Epidemiological Monitoring of Pemetrexed Use in Malignant Pleural Mesothelioma: A Tool of Local Decision Making. (12th March 2013) - Esposito, L; Palozzo, AC; Jirillo, A; Pasello, G; Favaretto, A; Paganelli, F
Abstract : Background: Pemetrexed is an expensive oncological drug, used in combination with platinum derivatives (cisplatin/carboplatin) in the first line treatment of unresectable malignant pleural mesothelioma. In Italy, this indication is no longer subject to web-based monitoring (Onco-AIFA Register) to ensure its use appropriateness. Purpose: To assess the effectiveness in patients treated at the Istituto Oncologico Veneto (IOV) compared to the pivotal trial. Materials and Methods: This observational analysis was performed on all patients with pleural mesothelioma treated at the IOV from 01/12/2006 to 30/04/2011; the data were extracted from both paper and computerised medical records. The median Overall Survival (OS) and Time To Progression (TTP) were calculated as updated on 31/05/2012 according to the intention to treat. Results: All 46 patients (32 males and 14 females) were evaluated in terms of OS. TTP was calculated only for the 41 evaluable patients (29 males and 12 females); 5 patients lost owing to lack of information at follow-up. The median OS/TTP values were respectively 14.2/8.9 months (vs. pivotal trial 12.1/5.7 months). The majority of patients received the less toxic protocol pemetrexed+carboplatin, which contributed to the better OS/TTP. Better OS/TTP might be related to the use in a neoadjuvant regimen (16 patients: 10 males and 6 females); a specific stratified analysis showed TTP/OS median of 27.8/18.6 months. Conclusions: To confirm the better effectiveness of the carboplatin+pemetrexed protocol, further data on a greater number of patients, neoadjuvant treatment, treatment toxicity and patient performance status are needed. Since the effectiveness of this high-cost oncological drug is not monitored at the national level, local monitoring is required to ensure appropriateness. The computerised medical record is a pre-requisite for protocol standardisation and a tool of information standardisation/updating. This work represents an easy, versatile methodological model with significant health implications. A widely shared computerised medical record is a powerful tool for epidemiological investigations; an established network allowing benchmarking is a valid and independent decision-making tool. No conflict of interest.